Comparative research on morphology and mechanical property of integument of Rana dybowskii, Xenopus laevis and Ambystoma mexicanum. (May 2021) - Li, Mo; Gao, Zibo; Dai, Taidong; Chen, Donghui; Tong, Jin; Guo, Li; Wang, Chaofei
Abstract: Amphibians' integument is a multifunctional organ offering protection from the exterior surroundings and facilitating the physiological change of gas, water and salts with the environment, which is a natural biomaterial with multifunctional features. Interspecies comparison of biomechanical characters and microstructure possibly related to them were performed on the integument of three species of amphibians, two anurans( Rana dybowskii and Xenopus laevis ) and one urodeles( Ambystoma mexicanum ) using tensile testing and morphological characterization. It was found that the integument of Rana dybowskii and Xenopus laevis was covered by polygonal epidermal cells, while the trunk surface of Ambystoma mexicanum presented irregular microstructure with the lack of keratinization. The integument of Rana dybowskii and Xenopus laevis exhibited good performance on stiffness and strength, which showed quite high mean elastic modulus, 931MPa and 1048MPa, respectively.